Methylene Blue Adsorption by Calcium Alginate Beads - RUKMANA (NIM : 10511086), DADAN
Methylene blue is a cationic dye which is commonly employed in textile industries. The dye is used for dyeing cotton, wool and silk. It is believed that dyeing in textile industry is respon sible for dyes pollutions into the water environment. The presence of dyes in water cause some negative effect on human health and environment. Alginate is a natural polysaccharide which has been widely used as adsorbent due to its carboxyl groups. Removal of methylene blue from aqueous solutions through adsorption on to calcium alginate beads (CA) and protonated calcium alginate beads (PCA) was studied. The adsorbents were characterized by FTIR and SEM. Effects of adsorption parameter such as initial pH, initial dye concentration, adsorbent mass and contact time are investigated. The uptake increased with solution pH and the optimum pH was found to be 5. The optimum initial concentration was 800 ppm with adsorption of 75% for CA and 87% for PCA. The optimum adsorbent mass was 0,05 grams, while the optimum contact time was 4 hours for CA and 3 hours for PCA. PCA have higher adsorption capacity to CA. Adsorption capacity for PCA and CA was 348,50 mg/g and 302,17 mg/g respectively. Both adsorbent were conformed to Langmuir adsorption isotherm and pseudo second order kinetic model. CA and PCA were used for adsorption-desorption cycles with desorption use HCl and HNO3 at concentrations 0,01 M; 0,1 M; 1 M and 2 M. Good desorbent for methylene blue desorption is HCl 2 M.